A comparative study related to job satisfaction in health institutions in İstanbul - Kaya, Gül Zahide (My University, 1999)
A Comparative Study Related To Job Satisfaction In Health Institutions in Istanbul This comparative study related to job satisfaction of 400 health personnel which consist of physicians , dentists , nurses , pharmacists , sanitarians , and midwives employed in Istanbul tests 36 null hypotheses at the . 05 level of significance and thereby examines the impacts of workplace status , occupation , length of service at the present workplace , level of education , age , gender on job satisfaction and its various facets namely ; work itself , supervision , pay , promotional opportunities and coworkers using ' Job Descriptive Index ' scale. The results demonstrate that health personnel in the private sector have significantly higher mean satisfaction point in relation to pay , work itself , coworkers , and mean overall job satisfaction yet lower mean satisfaction point in relation to supervision than health personnel in the public sector. Health personnel's occupation has significant effects on mean satisfaction point in relation to pay , supervision , work itself , coworkers , and mean overall job satisfaction point. Health personnel's length of service at the present workplace has significant effects on mean satisfaction point in relation to pay and work itself. Education level of health personnel has significant effects on mean satisfaction point in relation to pay , supervision , work itself and on mean overall job satisfaction. Health personnel's age has a significant effect on mean satisfaction point in relation to pay , work itself , coworkers and on mean overall job satisfaction. Female health personnel have significantly lower mean satisfaction point in relation to work itself , and mean overall job satisfaction point than male health personnel. KISA

Istanbul'daki Sağlık Kuruluşlarında İş Tatmini İle İlgili Karşılaştırmalı Bir Araştırma İstanbul'da çalışmakta olan doktor , hemşire , eczacı , sağlık memuru ve ebenin oluşturuğu toplam 400 sağlık personelinin katıldığı iş tatmini ile ilgili olan bu karşılaştırmalı çalışma , 36 sıfır hipotezi .05 anlamlılık düzeyinde test edilmiş ve bu suretle çalışılan kuruluşun statüsünün , mesleğin , çalışılan kuruluştaki görev süresinin , eğitim düzeyinin , yaşın ve cinsiyetin iş tatminine ve iş tatminin çeşitli boyutlarına ( işin kendisi , yönetim , ücret , terfi ve çalışma arkadaşları ) olan etkileri ' İş Betimlemesi Ölçeği ' kullanılarak araştırılmıştır. Sonuçlar göstermektedir ki ; özel sağlık kuruluşlarında çalışmakta olan sağlık personeli , kamu sağlık kuruluşlarında çalışmakta olan sağlık personeline göre anlamlı düzeyde daha yüksek ücret tatmini , işin kendisinden tatmin , iş arkadaşlığından tatmin ve bütünsel iş tatmini ; bununla beraber daha düşük yönetimden tatmin ortalama puanlarına sahiptir. Sağlık personelinin çalışmakta oldukları kuruluşlardaki görev süresinin işin kendisinden tatmin ve ücret tatmini ortalama puanları üzerinde anlamlı etkisi bulunmaktadır. Sağlık personelinin eğitim düzeyinin ücret tatmini , terfi tatmini , işin kendisinden tatmin ve bütünsel iş tatmini ortalama puanları üzerinde anlamlı etkisi bulunmaktadır. Sağlık personelinin yaşının ücret tatmini , işin kendisinden tatmin , çalışma arkadaşlığından tatmin ve bütünsel iş tatmini ortalama puanları üzerinde anlamlı etkisi bulunmaktadır. Kadın sağlık personeli , erkek sağlık personeline göre , anlamlı düzeyde daha düşük işin kendisinden tatmin ve bütünsel iş tatmini puanlarına sahiptir.
Keywords: İş tatmini; PERSONEL YÖNETİMİ,SAĞLIK HİZMETLERİNDE